FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PT PLN (PERSERO) UPT MALANG - Lutfiani Nur Adiliyah; Anik Malikah; M. Cholid Mawardi (Universitas Islam Malang, 2022)
This research aims to determine what factors can affect the performance of accounting information systems. The empirical study in this research is PT. PLN (Persero) in Malang. This type of research is quantitative research with multiple regression analysis method. the population in this study were employees of PT. PLN Persero UPT Malang. In this study using purposive sampling and obtained 32 respondents. The results of this study are the results of the study show that education and training have no significant effect on the performance of accounting information systems. The results showed that user involvement had no significant effect on the performance of accounting information systems. The top management support variable has a significant positive effect on the performance of the accounting information system.Keywords: accounting information system, education and training, user involvement, management support.